Transversus abdominis plane block in a canine undergoing to foreskin oncologic surgery - Ospina-Argüelles, Diego A. [UNESP]; Luís Vergara, S.; de Aquino, Patricia [UNESP] (Universidad Nacional Mayor de San Marcos, Vicerectorado de Investigacion, 2023)
The analgesic management performed on a 4.5-year-old male Boston Terrier who underwent resection of squamous cell carcinoma of the foreskin is described. Transverse abdominal plane block was performed with a lateral approach, using bupivacaine (0.25%) as local anaesthetic; complementing a multimodal analgesic protocol that also included acepromazine, meloxicam, dipyrone, fentanyl, ketamine, propofol, and isoflurane. Trans-surgical nociception was evaluated through the behaviour of non-invasive mean arterial pressure and heart rate. Immediate postoperative analgesia was assessed using the Glasgow Composite Pain Scale. Intraoperative cardiovascular parameters remained stable. The Glasgow scale score remained below the limit indicative of pain. It is suggested that the locoregional blockade associated with the analgesic protocol used made it possible to obtain a stable isoflurane amount and avoided the use of trans-surgical and postoperative rescue analgesia in the evaluated patient.
Bloqueo del plano abdominal transverso en un canino sometido a cirugía oncológica de prepucio
Keywords: anaesthesia; analgesia; dogs; nociception; pain; regional anaesthesia